Antibiotic perceptions, adherence, and disposal practices among parents of pediatric patients. - Keerti L Dantuluri; Kemberlee R Bonnet; David G Schlundt; Rebecca J Schulte; Hannah G Griffith; Alexandria Luu; Cara Charnogursky; Jessica M Perkins; Christine C Whitmore; Ritu Banerjee; Leigh M Howard; Carlos G Grijalva (PLoS ONE, 2023)
Antibiotics are frequently prescribed for children in the outpatient setting. Although sometimes necessary, antibiotic use is associated with important downstream effects including the development of antimicrobial resistance among human and environmental microorganisms. Current outpatient stewardship efforts focus on guiding appropriate antibiotic prescribing practices among providers, but little is known about parents' understanding of antibiotics and appropriate disposal of leftover antibiotics. To help bridge this gap, we conducted a qualitative study to assess parental understanding of their children's antibiotics, their adherence to antibiotic instructions, and their disposal practices. We conducted a semi-structured interview with parents of 13 children diagnosed with acute respiratory illnesses and prescribed antibiotics in an urban outpatient clinic. We found that parents had limited understanding of how antibiotics work. Although they received instructions about antibiotic use during the healthcare visit, adherence to the prescription and appropriate disposal of antibiotics was suboptimal. Limited baseline understanding of antibiotics, their prior experiences with antibiotics, perceptions about their social networks' antibiotic use, and information provided to them by healthcare providers may influence these behaviors. Our findings can inform educational efforts of outpatient stewardship programs to help optimize parental understanding of how to use and dispose of their children's antibiotics.